Lived experience in people with inflammatory bowel disease and comorbid anxiety and depression in the United Kingdom and Australia. (October 2021) - Mikocka-Walus, Antonina; Hanlon, Inna; Dober, Madeleine; Emerson, Catherine; Beswick, Lauren; Selinger, Christian; Taylor, Jo; Olive, Lisa; Evans, Subhadra; Hewitt, Catherine
This study explored the lived experience of people with inflammatory bowel disease and anxiety/depression. It utilised a deductive biopsychosocial framework. Overall, 24 patients and 20 healthcare professionals from two countries participated. In the United Kingdom, the main themes included (1) bidirectional relationship between inflammatory bowel disease and mental health, (2) the need for healthcare integration and (3) lack of awareness about the disease. In Australia, (1) the 'vicious cycle' of inflammatory bowel disease and psychosocial health, (2) the need for biopsychosocial healthcare integration and (3) the stigma of a hidden disease. Better communication around mental illness is essential in improving inflammatory bowel disease healthcare.